MISTISISME JAWA DALAM CERPEN ANJING-ANJING MENYERBU KUBURAN KARYA KUNTOWIJOYO: TINJAUAN REALISME MAGIS WENDY B. FARIZ - Windayanto, Riqko Nur Ardi (Fakultas Bahasa dan Sastra Indoensia, 2020)
This study aims to describe aspects of Javanese mysticism in the “Anjing-Anjing Menyerbu Kuburan” short story by Kuntowijoyo. This research uses qualitative method and descriptive approach. These aspects of mysticism are described with the five characteristics of the magical realism of Wendy B. Fariz's perspective, such as irreducible element, the phenomenal world, unsettling doubt, merging realms, and the disruptions of time, space and identity. The results showed that Javanese mysticism’s manifested in the form of pesugihan as a shortcut to achieve the wealth; and various magical objects, characters, and events. The socio-cultural background of the Javanese people, especially regarding to economic condition, also causes this practice of pesugihan.